INTERNATIONAL MARKETS EFFECT ON RICE PRICES IN THE REPUBLIC OF NORTH MACEDONIA - Lazo DIMITROV; Marija GJOSHEVA KOVACHEVIKJ; Sasho Kjosev (Ss Cyril and Methodius University in Skopje Faculty of Agricultural Sciences and Food - Skopje Republic of North Macedonia, 2022)
Abstract Agribusiness is one of North Macedonia’s most promising sectors. The aim of this work is to analyse the influence of international markets on rice prices in the Republic of North Macedonia. Data on the purchase price of rice have been analysed using statistical methods and models for the period from January 2005 to December 2021. A total of 204 months times series with data on the purchase price of rice for Macedonia, the EU, Greece, Italy and Spain have been analysed and compared. The Pearson correlation coefficient shows a relatively low relationship and mutual dependence of purchase prices in Macedonia, compared to prices in the EU, Greece, Italy and Spain. The purchase prices of rice in Macedonia in terms of the compared countries have the highest relationship and mutual dependence with the price movement in Italy (0.33), and the lowest with the price movement in the EU (0.08). The estimated lag length of the autoregressive process (AIC, BIC, FPE and HQIC tests), on average shows 2 lags (months) later time reaction of the rice prices in Macedonia with the comparison countries countries. The forecasting model (Granger causality test) shows that time series of prices can be convenient for forecasting rice prices in Macedonia.
Keywords: rice prices, international markets, agri-food prices, forecasting.